Cultivating Character Values About Tolerance in Kindergarten Permata Sunnah - Nurlela, Nurlela; Salsa Maulina, Besse; S. Malapata, Risma; Amalia Minatin, Nurul (PT Literasi Nusantara Publisher, 2022)
Character values are positive traits, character and personality that are useful for others. The purpose of this study was to describe the activities of inculcating character values through habituation and example of group A at RA Ihyaul Ulum Kedamean Gresik. The research method used in this research is descriptive qualitative research with a case study approach. Data collection techniques used are semi-structured interviews, participant observation, and documentation. Based on the results of research that has been carried out by researchers on the children of group A RA Ihyaul Ulum Kedamean Gresik, the character values that are observed and are often raised in this educational unit through habituation and example there are 7 characters, namely religious, responsibility, tolerance, discipline, friendly/communicative, peace-loving, and socially caring.